Molecular genetic maps of the group 6 chromosomes of hexaploid wheat (Triticum aestivum L. em. Thell.) - Marino, Celso L. [UNESP]; Nelson, James C.; Lu, Yun Hai; Sorrells, Mark E.; Leroy, Philippe; Tuleen, Neal A.; Lopes, Catalina R. [UNESP]; Hart, Gary E. (Canadian Science Publishing, 1996)
Restriction fragment length polymorphism (RFLP) maps of chromosomes 6A, 6B, and 6D of hexaploid wheat (Triticum aestivum L. em. Thell.) have been produced. They were constructed using a population of F 7-8 recombinant inbred lines derived from a synthetic wheat X bread wheat cross. The maps consist of 74 markers assigned to map positions at a LOD ≥ 3 (29 markers assigned to 6A, 24 to 6B, and 21 to 6D) and 2 markers assigned to 6D ordered at a LOD of 2.7. Another 78 markers were assigned to intervals on the maps. The maps of 6A, 6B, and 6D span 178, 132, and 206 cM, respectively. Twenty-one clones detected orthologous loci in two homoeologues and 3 detected an orthologous locus in each chromosome. Orthologous loci are located at intervals of from 1.5 to 26 cM throughout 70% of the length of the linkage maps. Within this portion of the maps, colinearity (homosequentiality) among the three homoeologues is strongly indicated. The remainder of the linkage maps consists of three segments ranging in length from 47 to 60 cM. Colinearity among these chromosomes and other Triticeae homoeologous group 6 chromosomes is indicated and a consensus RFLP map derived from maps of the homoeologous group 6 chromosomes of hexaploid wheat, tetraploid wheat, Triticum tauschii, and barley is presented.
Keywords: Linkage maps; Molecular markers; RFLP; Wheat